2021
DOI: 10.1177/23982128211007769
|View full text |Cite|
|
Sign up to set email alerts
|

Hot and cold executive functions in the brain: A prefrontal-cingular network

Abstract: Executive functions, or cognitive control, are higher-order cognitive functions needed for adaptive goal-directed behaviours and are significantly impaired in majority of neuropsychiatric disorders. Different models and approaches are proposed for describing how executive functions are functionally organised in the brain. One popular and recently proposed organising principle of executive functions is the distinction between hot (i.e. reward or affective-related) versus cold (i.e. purely cognitive) domains of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 155 publications
(215 reference statements)
2
111
0
8
Order By: Relevance
“…However, neither their nor our finding suggest an acute enhancing effect of anodal tDCS over F3 on problem solving. However, the previous and our finding might need to be interpreted within a recent theoretical framework that divides executive functions into "hot" executive functions related to reward, emotion and motivation such as emotion regulation, delay discounting and risky and affective decision making and purely, cognitive "cold" executive functions such as working memory, response inhibition, cognitive flexibility and planning ability [43]. As problem solving and planning ability have in healthy participants recently been shown to not be a purely "cold" but also to a certain extent a "hot" executive functions, it is possible that our stimulation parameters were not optimal for the Tower of London task [44].…”
Section: Plos Onementioning
confidence: 84%
“…However, neither their nor our finding suggest an acute enhancing effect of anodal tDCS over F3 on problem solving. However, the previous and our finding might need to be interpreted within a recent theoretical framework that divides executive functions into "hot" executive functions related to reward, emotion and motivation such as emotion regulation, delay discounting and risky and affective decision making and purely, cognitive "cold" executive functions such as working memory, response inhibition, cognitive flexibility and planning ability [43]. As problem solving and planning ability have in healthy participants recently been shown to not be a purely "cold" but also to a certain extent a "hot" executive functions, it is possible that our stimulation parameters were not optimal for the Tower of London task [44].…”
Section: Plos Onementioning
confidence: 84%
“…These findings primarily suggest that vmPFC activation, compared to r-TPJ activation, seems to be more involved in reading mental states and social cognition in autism. Previous neuroimaging studies have repeatedly shown that a frontal-posterior network is activated during ToM and social cognition, including the medial PFC, posterior cingulate cortex and TPJ (Barch et al, 2013;Boccadoro et al, 2019;Gallagher et al, 2000;Salehinejad et al, 2021;Van Overwalle, 2009). In ASD, these regions are usually underactive compared to healthy controls (Kana et al, 2015) implicating that increasing their activity could enhance ToM ability.…”
Section: Discussionmentioning
confidence: 99%
“…In ASD, which is marked by poor ToM ability, neuroimaging studies have shown altered activation and connectivity of this frontal-posterior network, and specifically the vmPFC and TPJ (Kana et al, 2015;Nijhof, Bardi, Brass, & Wiersema, 2018;Yuk, Anagnostou, & Taylor, 2020). These regions, which are part of a prefrontal-cingular network, are highly engaged in ASD reciprocity abilities (Salehinejad et al, 2021). Such alternation of activity is in general accordance with the broader pathophysiology of ASD that results from early altered brain development and neural reorganization (Lord et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, the neural network structure that serves as a substrate for executive functioning suggests that both cold and warm EF operate simultaneously in everyday life, except for dysfunctions [ 14 ]. The neural substrate for EF lies through multiple frontal-subcortical pathways among which a predominantly dorsolateral pathway is identified for cold EF processes and an orbitofrontal/ventromedial pathway for warm EF [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%